Pelatihan Pengolahan Data Statistik Sederhana Menggunakan Spreadsheet untuk Mendukung Pengambilan Keputusan Organisasi Siswa (OSIS) di Kelurahan Kunciran - Annisa Tsamratul"ain; Indah Sataria (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
Decision-making in student organizations is often still based on subjective intuition due to low data literacy among board members. This Community Service (PKM) activity aims to improve the skills of OSIS (Student Council) members in Kunciran Village, Tangerang City, in processing simple statistical data using spreadsheet applications as a basis for accountable organizational decision-making. The implementation method involved participatory workshops including administrative problem identification, descriptive statistics function training, and work program survey data visualization practice. The results showed a significant increase in participants' technical skills, with a 56% increase in survey data processing functions and a 50% increase in data visualization techniques. Through this training, OSIS members were able to transform raw data into strategic information that supports reporting transparency and program evaluation effectiveness. This activity concludes that mastering appropriate office software is an essential foundation for adaptive student leadership in the digital era.